Role of Information and Communication Technology on Competitive Advantage of Hotels: A Case Study of Cephas Inn Hotel. - Mubangizi, Elijah (Kabale University, 2024)
The study investigated the impact of information and communication technology (ICT) on the competitive advantage of hotels, focusing on Cephas Inn Hotel as a case study. The objectives included identifying the types of ICT applications used at Cephas Inn Hotel in Kabale, examining the benefits of competitive advantage for the hotel, and establishing the roles of ICT in enhancing this competitive advantage. A cross-sectional study design was employed, with data collected through interviews and questionnaires. Findings revealed that among the types of ICT applications at Cephas Inn Hotel, the majority of respondents cited the use of cameras, while a few mentioned the hotel management system. Regarding the benefits of competitive advantage, most respondents indicated that it resulted in an increased market share, while a smaller number noted it enhanced profitability. In terms of the roles of ICT in fostering competitive advantage, many respondents highlighted that ICT improved efficiency, guest satisfaction, and overall performance; however, fewer respondents pointed out that ICT facilitated the creation of visually appealing and user-friendly websites, which encouraged online bookings. The study recommended that hotels invest in enhancing IT competencies through training programs to better align IT investments with internal capabilities and organizational processes.